Internet Videoconferencing in undergraduate paramedic education. - Williams, Brett (Journal of Emergency Primary Health Care, 2010)
This paper illustrates the innovative use of Internet Videoconferencing in a blended and case-based learning approach used to support undergraduate paramedic student learning during weekly clinical problems. Regular Internet Videoconferencing learning periods were offered to students by teaching staff, increasing after-hours communication opportunities otherwise not normally achievable. Whilst encouraging learning outcomes were achieved with some students, other students encountered barriers such as lack of available bandwidth, inappropriate computer hardware and preference for face-to-face contact.